High Fibrinogen Level is An Independent Predictor of Presence and Severity of Coronary Artery Disease (Cardiovascular Journal, 2014)
Background: Fibrinogen has been identified as an independent risk factor for cardiovascular disease and associated with traditional cardiovascular risk factors. Few reports have so far investigated the relationship between fibrinogen levels and the extent of coronary artery disease (CAD) as evaluated by coronary angiography. Therefore the current study was carried out to evaluate the relationship between fibrinogen levels and the extent of CAD as evidenced by coronary angiography. Method: A total of 210 patients having ischemic heart disease including chronic stable angina, unstable angina, non-ST elevated myocardial infarction & ST elevated myocardial infarction were evaluated in National Institute of Cardiovascular Disease (NICVD), Dhaka with a view to find out the relationship between fibrinogen levels and the extent of CAD undergoing coronary angiography. Patients were divided in 3 groups according to fibrinogen levels: Group I = fibrinogen levels 600 mg/dl. In this study, angiographic severity was assessed by vessel score, stenosis score and lesion morphology and tries to find out their relationship with angiographic severity and fibrinogen level. Result: Using a prospective analytic design we studied 210 patients who were divided into 3 groups : Vessel score in Group I, Group II & Group III were 1.14 ± 0.56, 2.24 ± 0.58, & 3.00 ± 0.65 respectively which was statistically significant (p < 0.01) and Stenosis score in group- I, group- II & group- III were 6.00 ± 4.19, 18.72 ± 4.94, & 32.41 ± 15.75 respectively which was statistically significant (p < 0.01). Regarding morphology of the lesions, complex lesions in group I, group II & group III were 21%, 32% & 39% respectively (statistically significant; p < 0.01). Conclusion: High fibrinogen level is independently and significantly associated with more severe coronary artery disease. Serum fibrinogen can be used as a new and even simpler tool for risk stratification in acute coronary syndrome. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20784 Cardiovasc. j. 2014; 7(1): 4-10